2005
DOI: 10.1074/jbc.m505777200
|View full text |Cite
|
Sign up to set email alerts
|

A Flagellum-specific Calcium Sensor

Abstract: The flagellar calcium-binding protein (FCaBP) of the flagellated protozoan Trypanosoma cruzi associates with the flagellar membrane via its N-terminal myristate and palmitate moieties in a calcium-modulated, conformation-dependent manner. This mechanism of localization is similar to that described for neuronal calcium sensors, which undergo calcium-dependent changes in conformation, which modulate the availability of the acyl groups for membrane interaction and partner association. To test whether FCaBP underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 40 publications
(56 reference statements)
1
43
0
Order By: Relevance
“…A single flagellum membrane-specific protein, the ESAG4 adenylate cyclase, has been identified in T. brucei (Paindavoine et al, 1992), and a calcium-binding flagellar membrane protein has been characterized in T. cruzi (Engman et al, 1989;Buchanan et al, 2005). In the flagellar matrix, several components of the intraflagellar transport pathway (IFT20, IFT52, IFT172) have recently been shown to exhibit both a soluble flagellar pool and a detergent-insoluble basal body-associated pool (Absalon et al, 2007a), but no other soluble flagellar proteins have been identified.…”
Section: Flagellar Membrane and Matrixmentioning
confidence: 99%
“…A single flagellum membrane-specific protein, the ESAG4 adenylate cyclase, has been identified in T. brucei (Paindavoine et al, 1992), and a calcium-binding flagellar membrane protein has been characterized in T. cruzi (Engman et al, 1989;Buchanan et al, 2005). In the flagellar matrix, several components of the intraflagellar transport pathway (IFT20, IFT52, IFT172) have recently been shown to exhibit both a soluble flagellar pool and a detergent-insoluble basal body-associated pool (Absalon et al, 2007a), but no other soluble flagellar proteins have been identified.…”
Section: Flagellar Membrane and Matrixmentioning
confidence: 99%
“…6) and of the trypanosome flagellar membrane proteome (10) have identified flagellar membrane proteins likely to be involved in signal transduction, including potential kinases, adenylate cyclases, and Ca 2ϩ channels. Indeed, the Trypanosoma cruzi Flagellar Ca 2ϩ Binding Protein (TcFCaBP) is localized specifically to the parasite flagellar membrane and has been suggested to have a role in Ca 2ϩ -dependent signal transduction (11)(12)(13). As demonstrated some years ago, the adenylate cyclase ESAG-4 is also targeted to the flagellar membrane in Trypanosoma brucei (14).…”
mentioning
confidence: 99%
“…17 T. brucei Tb24 and T. cruzi FCaBP may also differ by interacting with distinct membranebound protein targets. 18,19 Atomic resolution structures of T. brucei FCaBPs are needed to elucidate their Ca 2þ -induced conformational changes that control membrane-targeting. We report here the NMR structure for Ca 2þ -free calflagin Tb24 (henceforth referred to simply as Tb24).…”
mentioning
confidence: 99%